2015
DOI: 10.1007/s10681-015-1595-9
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridisation of cytoplasmic male-sterile rapeseed with Ogura cytoplasm and Brassica rapa var. pekinensis as a method to obtain male-sterile Chinese cabbage inbred lines

Abstract: During 2011-2014, three self-compatible Chinese cabbage inbred lines (Brassica rapa, genome AA 2n = 20) were sexually hybridised with cytoplasmic male-sterile (CMS Ogu-INRA) and fertile lines of rapeseed (Brassica napus var. oleifera, genome AACC 2n = 38). Interspecific F 1 hybrids and their consecutive back-crosses (BCs) toward B. rapa were obtained, and their morphological and commercial characteristics, as well as their ability for generative propagation, were analysed. Cytometric and morphological analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…These improved CMS lines are known as Ogu‐INRA and are widely used to produce hybrids in Brassicaceae (Pelletier and Budar , Kaminski et al. ). Extensive research on Ogura cytoplasm has revealed the molecular basis of male sterility and fertility restoration (Bonhomme et al.…”
Section: Pollination Control Methods In Different Vegetable Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…These improved CMS lines are known as Ogu‐INRA and are widely used to produce hybrids in Brassicaceae (Pelletier and Budar , Kaminski et al. ). Extensive research on Ogura cytoplasm has revealed the molecular basis of male sterility and fertility restoration (Bonhomme et al.…”
Section: Pollination Control Methods In Different Vegetable Cropsmentioning
confidence: 99%
“…, Kaminski et al. ). Another source of new CMS lines is protoplast fusion, where recombination between the two parental mitochondrial genomes occurs prior to cytoplasmic segregation in the somatic hybrids (Rambaud et al.…”
Section: Types Of Pollination Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural distant hybridization is the main driving force for species formation [43] and interspecies hybridization usually leads to cytoplasmic male sterility because of species isolation [44][45][46]. The artificial wide crossing is a process to mimic the evolution in nature to select elite descendent with favorable agronomic traits.…”
Section: Dosage Effect and Rna-editing Play Predominant Roles In Planmentioning
confidence: 99%
“…rapa) and radish (Raphanus sativus L.) and an important oil crop, oilseed rape (Brassica napus L.). Hybrid seed production in these crops has been developed worldwide using Ogura male sterile cytoplasm discovered in a Japanese radish (Raphanus sativus L.) and introgressed in B. oleracea by repeated backcrosses (Yamagishi and Bhat, 2014;Kaminski et al, 2016;Sekhon et al, 2018). However, these initial alloplasmic male sterile lines carrying Ogura cytoplasm presented chlorophyll deficiency at low temperatures, underdeveloped nectaries and malformed ovaries and pods which reduced the seed set.…”
Section: Brassicaceasmentioning
confidence: 99%